Inhibition Effect of Ethyl Acetate Soluble Fraction of Citrullus colocynthis on In Vitro Cholesterol Crystallization - Sampath Kumar, N.; Madhurambal, G. (Asian Journal of Chemistry, 2011)
Cholesterol is one of the important compounds in the body for the proper function of several systems. When the presence of cholesterol exceeds its maximum level it leads to cardiovascular disease (CVD) which is due to the deposition (crystallization) of cholesterol on the interior sides of the blood vessels. The crystallization depends on factors like solvents, concentration, pH and temperature. The crystallization process can be affected by the presence of phytoactive compounds like flavanoids, terepenoids, triterepenoids etc. Phytoactive compounds present in the ethyl acetate fraction of the fruits of Citrullus colocynthis are capable of altering the rate of crystallization and the morphology of the crystals when they are introduced to the in vitro crystallization process.